Building A Social Edition of the Devonshire Manuscript - Crompton, Constance; Powell, Daniel; Arbuckle, Alyssa; Siemens, Ray; Shirley, Maggie (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
This article describes the context and development of A Social Edition of the Devonshire Manuscript, a collaboratively created Wikibook edition of the sixteenth-century verse miscellany known as the Devonshire Manuscript (BL MS Add. 17,492). This project began in 2001 when Dr. Ray Siemens led a group of researchers in an exploration of how to create a digital edition of the Devonshire Manuscript. Since then, the project has transitioned through many forms and formats, and A Social Edition of the Devonshire Manuscript is the most recent output of these academic experiments. Of note, a print version of A Social Edition of the Devonshire Manuscript is forthcoming from Iter and Medieval and Renaissance Texts and Studies (MRTS).